Progress in Emerging Contaminants Removal by Adsorption/Membrane Filtration-Based Technologies: A Review - Rosmaya Dewi; Norazanita Shamsuddin; Muhammad S. Abu Bakar; Jose H. Santos; Muhammad Roil Bilad; Lee Hoon Lim (Universitas Pendidikan Indonesia, 2021)
This paper discussed the removal and the remediation of emerging contaminants (ECs) in water using adsorption and membrane filtration as a single and hybrid system. The classifications, sources, effects, detection techniques, and available technologies for ECs removal were discussed. Next, an overview of both adsorption and membrane filtration processes in terms of materials, separation mechanisms, factors affecting their performances, and their applications for ECs removals was provided. It was followed by a comprehensive review of the combination of the membrane and the adsorption processes with other physical, chemical, or biological treatments. Finally, progress in research on a hybrid system between membrane filtration and adsorption was discussed. The combination included adsorption as the pre-treatment, integrated adsorption/membrane filtration system, or adsorption as the post-treatment. Generally, the hybrid systems showed improved performance than a single system. Nonetheless, further studies are recommended for applications of those systems on a wide range of ECs removals and the scale-up issue.